Interaction among three viruses in naturally infected potato cultivars - S.M. PAUL KHURANA, SHATRUGHNA SINGH and (Indian Phytopathology, 2002)
The concentration of potato virus Y (PVY), potato virus X (PVX) and potato virus S (PVS) occurring singly or in co-infections (with two or three viruses under field conditions) were checked in five Indian commercial potato cultivan. An increased PVX concentration in doubly infected (PVY + PVX) plants was recorded only in PVY-susceptible cultivar Kufri, Chandtamukhi as against reduced PVX concentration observed in PVY-tolerant cultivar Kufri Sindhuri. Similarly, reduced PVY concentration was recorded in doubly (PVY + PVX) infected PVX-reststant cultivar Kufri Lalima. PVS concentration was also reduced in PVY tolerant cultivar Kufri Sindhuri when the plants were co-infected with all the three viruses. Besides, PVX concentration was reduced in presence of PVS only in cuhivar Kufri Lauvkar.